Oxidative stress in preeclampsia and the role of free fetal hemoglobin - Hansson, Stefan R.; Nääv, Åsa; Erlandsson, Lena (Frontiers in Physiology, 2015)
Preeclampsia is a leading cause of pregnancy complications and affects 3–7 % of pregnant women. This review summarizes the current knowledge of a new potential etiology of the disease, with a special focus on hemoglobin-induced oxidative stress. Furthermore, we also suggest hemoglobin as a potential target for therapy. Gene and protein profiling studies have shown increased expression and accumulation of free fetal hemoglobin in the preeclamptic placenta. Predominantly due to oxidative damage to the placental barrier, fetal hemoglobin leaks over to the maternal circulation. Free hemoglobin and its metabolites are toxic in several ways; a) ferrous hemoglobin (Fe2+) binds strongly to the vasodilator nitric oxide and reduces the availability of free nitric oxide, which results in vasoconstriction, b) hemoglobin (Fe2+) with bound oxygen spontaneously generates free oxygen radicals and c) the heme groups create an inflammatory response by inducing activation of neutrophils and cytokine production. The endogenous protein α1-microglobulin, with radical and heme binding properties, has shown both ex vivo and in vivo to have the ability to counteract free hemoglobin-induced placental and kidney damage. Oxidative stress in general, and more specifically fetal hemoglobin-induced oxidative stress, could play a key role in the pathology of preeclampsia seen both in the placenta and ultimately in the maternal endothelium.